THU0362 Aa Amyloidosis Treated by Tocilizumab: Efficacy in Inflammatory And/Or Anti-TNF Alpha Refractory Forms - an International Study. (10th June 2014) - Courties, A.; Grateau, G.; Philippe, P.; Flipo, R.-M.; Astudillo, L.; Aubry-Rozier, B.; Fabreguet, I.; Fahd, W.; Fain, O.; Guggenbuhl, P.; Hachulla, E.; Papo, T.; et al.
Abstract : Background: In published case reports, tocilizumab (TCZ) exhibits a brilliant efficacy on AA amyloidosis in almost all patients 1 . Objectives: We investigated the efficacy and safety of TCZ in AA amyloidosis in a multicentric study of unselected cases. Methods: Using the Club Rhumatismes Inflammation (CRI) network and the French TCZ registry REGATE, we contacted by mail rheumatology and internal medicine departments from France, Switzerland and North Africa to gather data from consecutive patients with histologically proven AA amyloidosis who were treated by at least 1 TCZ infusion. Efficacy was defined as a sustained decrease of proteinuria and/or stable or improved glomerular filtration rate (GFR) as well as by the TCZ maintenance. Results: Twelve AA amyloidosis patients were treated by TCZ in monotherapy (mean ± SD age 63±16.2 years, amyloidosis duration 20.6±31.4 months). Eight patients had rheumatoid arthritis (RA) whose 6 who have previously failed to anti-TNF. Eleven patients had renal involvement with 2 patients already in haemodialysis (not included in the renal efficacy assessment). For the nine others, baseline GFR and proteinuria were 53.6±32.8 mL/min and 5±3.3 g/24h. TCZ was efficient on 6 cases of 8 RA patients (87.5%) according to EULAR response (4 good and 2 moderate responders). As expected, all CRP decreased. Renal amyloidosis (n=9) progressed in 3 patients and was stabilized in 3 patients. Three patients improved since they experienced a sustained decrease in proteinuria (of 42%, 82% and 96% respectively). Patients who responded or stabilized under TCZ had a higher CRP level at baseline or a proteinuria due to nephrotic syndrome with a preserved GFR at baseline (Table). Among the 6 RA patients previously treated by anti-TNF, amyloidosis was improved in 1 and was stabilized in 3 cases. Three serious adverse events occurred (2 diverticulitis and 1 major calciphylaxia due to renal failure). Finally, 7/12 (58%) patients pursued TCZ. Conclusions: Efficacy of TCZ in AA amyloidosis is variable depending on the severity of the renal disease and on the inflammatory status at the treatment onset. Discrepancy between our study on unselected consecutive patients and the reported cases in the literature may be explained by publication bias. TCZ should be proposed as early as possible in the course of renal AA amyloidosis and in patients who are refractory to anti-TNF therapy. References: Hakala M et al Ann Rheum Dis 2013;72:464-5. Disclosure of Interest: : A. Courties Shareholder of: none, Grant/research support: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, G. Grateau Shareholder of: none, Grant/research support: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, P. Philippe Shareholder of: none, Grant/research support: Roche-Chugai, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, R.-M. Flipo Shareholder of: none, Grant/research support: Roche-Chugai, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, L. Astudillo Shareholder of: none, Grant/research support: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, B. Aubry-Rozier Shareholder of: none, Grant/research support: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, I. Fabreguet Shareholder of: none, Grant/research support: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, W. Fahd Shareholder of: none, Grant/research support: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, O. Fain Shareholder of: none, Grant/research support: Roche-Chugai, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, P. Guggenbuhl Shareholder of: none, Grant/research support: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, E. Hachulla Shareholder of: none, Grant/research support: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, T. Papo Shareholder of: none, Grant/research support: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, C. Richez Shareholder of: none, Grant/research support: Roche-Chugai, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, J. Sibilia Shareholder of: none, Grant/research support: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, J. Morel Shareholder of: none, Grant/research support: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, F. Berenbaum Shareholder of: none, Grant/research support: Roche-Chugai, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, J. Sellam Shareholder of: none, Grant/research support: Roche-Chugai, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none DOI: 10.1136/annrheumdis-2014-eular.2343